Habituation After Deep Brain Stimulation in Tremor Syndromes: Prevalence, Risk Factors and Long-Term Outcomes - Peters, James; Tisch, Stephen (Frontiers in Neurology, 2021)
Deep brain stimulation (DBS) of the thalamus is an effective treatment for medically refractory essential, dystonic and Parkinson's tremor. It may also provide benefit in less common tremor syndromes including, post-traumatic, cerebellar, Holmes, neuropathic and orthostatic tremor. The long-term benefit of DBS in essential and dystonic tremor (ET/DT) often wanes over time, a phenomena referred to as stimulation “tolerance” or “habituation”. While habituation is generally accepted to exist, it remains controversial. Attempts to quantify habituation have revealed conflicting reports. Placebo effects, loss of micro-lesional effect, disease related progression, suboptimal stimulation and stimulation related side-effects may all contribute to the loss of sustained long-term therapeutic effect. Habituation often presents as substantial loss of initial DBS benefit occurring as early as a few months after initial stimulation; a complex and feared issue when faced in the setting of optimal electrode placement. Simply increasing stimulation current tends only to propagate tremor severity and induce stimulation related side effects. The report by Paschen and colleagues of worsening tremor scores in the “On” vs. “Off” stimulation state over time, even after accounting for “rebound” tremor, supports the concept of habituation. However, these findings have not been consistent across all studies. Chronic high intensity stimulation has been hypothesized to induce detrimental plastic effects on tremor networks, with some lines of evidence that DT and ET may be more susceptible than Parkinson's tremor to habituation. However, Tsuboi and colleague's recent longitudinal follow-up in dystonic and “pure” essential tremor suggests otherwise. Alternatively, post-mortem findings support a biological adaption to stimulation. The prevalence and etiology of habituation is still not fully understood and management remains difficult. A recent study reported that alternating thalamic stimulation parameters at weekly intervals provided improved stability of tremor control consistent with reduced habituation. In this article the available evidence for habituation after DBS for tremor syndromes is reviewed; including its prevalence, time-course, possible mechanisms; along with expected long-term outcomes for tremor and factors that may assist in predicting, preventing and managing habituation.